Apixaban as a Rare Cause of Leukocytoclastic Vasculitis. (27th February 2020) - Spears, Jenna; Chetrit, David Alexandre; Manthey, Sina; Lee, Christopher; Al-Saiegh, Yousif
Abstract : Apixaban is a rare cause of leukocytoclastic vasculitis (LCV). To our knowledge, there is only one other reported case due to apixaban in the literature. We present a case of apixaban-induced leukocytoclastic vasculitis in a 95-year-old male. He had been started on apixaban 12 days prior to presentation and developed worsening palpable purpura of his lower extremities. Possible etiologies of this new rash were excluded, with biopsy showing extensive purpura with superficial perivascular neutrophilic infiltrate and leukocytoclasis. Apixaban was discontinued, and the patient was started on a slow prednisone taper with subsequent resolution of his rash.